Основатель научной школы "промышленной социологии" В.Г.Подмарков - Тростановский, Ж. (Социология: теория, методы, маркетинг, 1999)
The essay is about life, works, valuable contribution to sociology of the USSR, and civic believes of professor V.G.Podmarkov, prominent researcher of Soviet social science. Being a founder of industrial sociology, he raised a numerous group of highly qualified sociologists. Professor Podmarkov was a forerunner of the changes success of which would greatly affect the future of our country.